2006
DOI: 10.1002/cncr.21993
|View full text |Cite
|
Sign up to set email alerts
|

DNA ploidy compared with human papilloma virus testing (Hybrid Capture II) and conventional cervical cytology as a primary screening test for cervical high‐grade lesions and cancer in 1555 patients with biopsy confirmation

Abstract: BACKGROUND.Because 80% of cervical cancers arise in low‐resource settings, many inexpensive strategies are being tested. In that spirit, the authors are testing large‐scale genomic or DNA ploidy measurements as an inexpensive and semiautomated strategy.METHODS.Patients entered either a screening or diagnostic study of several optical technologies: quantitative cytology, quantitative histopathology, and fluorescence and reflectance spectroscopy using a point probe, a multispectral digital colposcope, or a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 65 publications
4
70
0
Order By: Relevance
“…In our study, we found that the cut off value of 5c for aneuploidy determined by automated DNA ICM used for cervical and esophageal cancer detection [5,6,16] and 4.6c use for oral cancer detection should not be used as threshold values for effusion cytology diagnosis, as it is not as robotic as the 2.5c we identified. This is due to the fact that malignant cells in cervical, esophageal and oral cancer are squamous cell carcinoma while malignant cells in effusion are largely adenocarcinoma.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In our study, we found that the cut off value of 5c for aneuploidy determined by automated DNA ICM used for cervical and esophageal cancer detection [5,6,16] and 4.6c use for oral cancer detection should not be used as threshold values for effusion cytology diagnosis, as it is not as robotic as the 2.5c we identified. This is due to the fact that malignant cells in cervical, esophageal and oral cancer are squamous cell carcinoma while malignant cells in effusion are largely adenocarcinoma.…”
Section: Discussionmentioning
confidence: 72%
“…The system consisted of a computer controlled motorized microscope and high-resolution digital camera for image scanning and capturing, and software for controlling of image scanning, processing and analysis. The software used for the automatic classification of cells, measurement of DNA ploidy and analysis of aneuploidy was derived from the British Columbia Cancer Agency, Vancouver, Canada [16]. For each slide, 1000 cell nuclei or all of the cell nuclei on the slide were scanned and nuclear images were collected into a nuclear DNA image gallery.…”
Section: Automated Dna Icmmentioning
confidence: 99%
See 1 more Smart Citation
“…One of criteria is measurement of nuclear DNA content together with set of features for cell morphology recognition such as nuclear to cytoplasm ratio. This method was described and used previously (Guillaud et al, 2006) All scanned slides were first reviewed by trained technician who had 2-5 years of experience. Cervical cytology reports were classified according to Bethesda (TBS) diagnostic system and were reported as: ASCUS, ASC-H, LSIL, HSIL, cancer and other positive.…”
Section: Slide Analysis and Readingmentioning
confidence: 99%
“…These three changes form the basis for the biological basis for the adoption on new technologies. Table 1 shows endoscope-compatible optical technologies and their role in cancer screening and detection in all organ sites [19]. We know that as intraepithelial neoplasia develops, it secretes growth factors that increase the vasculature to supply nutrients to the lesion.…”
mentioning
confidence: 99%